An unusual case report of transcatheter aortic valve implantation-related actinomycosis endocarditis. Issue 8 (28th August 2022) - Gurevitz, Chen; Rubchevsky, Victor; Hamdan, Ashraf; Orvin, Katia
Abstract: Background: Actinomycosis is a chronic invasive infection caused by Actinomyces species. Actinomycosis endocarditis has been described, yet considered rare. We present the first reported transcatheter aortic valve implantation (TAVI)-related actinomycosis endocarditis. Case summary: A 70-year-old female patient, presented 4 months after TAVI with malaise and vocal-cord paralysis. She underwent computed tomography angiography which demonstrated a 28 mm pseudoaneurysm of the ascending aorta, which compressed the laryngeal nerves. Her condition rapidly deteriorated with cardiogenic shock and required an emergent surgery, which reviled a tamponade with active bleeding, due to an ascending aortic dissection. She underwent aortic valve and ascending aorta replacement. A 2 cm vegetation was found on the TAVI prosthetic valve and sent for cultures, which later revealed an Actinomyces neuii infection. Long-term intravenous ampicillin treatment was given. Discussion: This case describes a patient with endocarditis on TAVI prosthetic valve, with an unusual clinical presentation and rapid deterioration to an emergency intervention. This unique presentation of tumour-like tissue invasion is characteristic of actinomycosis, and should be suspected especially following valve replacement.